Genome-Wide Association Studies of Drug-Resistance Determinants. Issue 3 (March 2017) - Volkman, Sarah K.; Herman, Jonathan; Lukens, Amanda K.; Hartl, Daniel L.
Abstract : Population genetic strategies that leverage association, selection, and linkage have identified drug-resistant loci. However, challenges and limitations persist in identifying drug-resistance loci in malaria. In this review we discuss the genetic basis of drug resistance and the use of genome-wide association studies, complemented by selection and linkage studies, to identify and understand mechanisms of drug resistance and response. We also discuss the implications of nongenetic mechanisms of drug resistance recently reported in the literature, and present models of the interplay between nongenetic and genetic processes that contribute to the emergence of drug resistance. Throughout, we examine artemisinin resistance as an example to emphasize challenges in identifying phenotypes suitable for population genetic studies as well as complications due to multiple-factor drug resistance. Trends: Overlaying different genetic tests for association, selection, and linkage can increase the likelihood of identifying genetic variants responsible for drug resistance. Artemisinin resistance is mediated by mutations in the kelch13 locus, but other interacting partners or pathways may be involved in modulating this resistance. Genetic variants responsible for resistance to partner drugs paired with artemisinin-based compounds in combination therapy are a growing concern and may involve multiple loci and copy-number variations as well as nucleotide changes. Technological advances in generating and analyzing genome sequences to identify copy-number variations as well as SNPs directly from patient isolates promise to aid the discovery of drug-resistance loci. Increasing use of drugs for malaria elimination campaigns will likely alter parasite population structure and increase drug resistance, and it will be a challenge for genome-wide association studies to identify drug-resistance loci from among a largely shared genetic background. Increasing awareness of 'anti-correlated' drug combinations that are active against alternative allelic versions of the target locus are changing the way drug combinations may be deployed and provide opportunities for novel combination therapies or strategies to offset or reduce the risk of emerging drug resistance.